Nurse role in the prevention of infections of the oncology patient with fever neutropenic - Imilia Torres Orue; Beatriz Rodríguez Alonso; Ana Ibis Jiménez Hernández; Alejandro Castillo Garcet (Fundación para el Desarrollo de la Enfermería, 2011)
The neutropenia post chemotherapy this identified one as the factor that but it predisposes the infection in patient with cancer; because the neutrófilos constitutes the main system of defence of the organism. Keeping in mind the list that the infirmary personnel should develop in the prevention of the infections in these patients, he was carried out a documental revision modernized on the topic with the objective of the infirmary actions that contribute to prevent the infections in the patient neutropenico and to improve his quality of life settling down. They were used for it the methods theoretical analysis - synthesis and induction-deduction. The male nurse, as active member of the medical team is key in the prevention of infections to the patient neutropenico, because his cares are guided to complete measures of hygiene and comfort, to assure the patient´s appropriate nutrition and to offer education and support measures; what favours to re-establish, to conserve and to promote, the health of the oncology patient with neutropenic.